2023
DOI: 10.1007/s13300-023-01491-5
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin-Induced Myocardial Flow Reserve Improvement is not Associated with HDL Ability to Stimulate Endothelial Nitric Oxide Production

Umberto Capece,
Chiara Pavanello,
Francesca Cinti
et al.

Abstract: Background Sodium-glucose cotransporter-2 (SGLT2) inhibitors have shown controversial results in modulating plasma lipids in clinical trials. Most studies found slight increases in high-density lipoprotein (HDL) cholesterol but few have provided evidence on HDL functionality with disappointing results. However, there is broad agreement that these drugs provide cardiovascular protection through several mechanisms. Our group demonstrated that dapagliflozin improves myocardial flow reserve (MFR) in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In addition, in patients with type 2 diabetes, SGLT2 inhibition improves myocardial blood flow reserve measured using 13 N-ammonia PET/CT raising the possibility of a benefit from SGLT2 inhibition in the microvascular angina population. 29 This suggests a similar strategy to that used in the ZENITH-CKD trial combining low-dose zibotentan with an SGLT-2 inhibitor may be additive NMED-A129750A from the efficacy point of view and mitigate fluid retentive effects of the endothelin A antagonist. 18,30 Limitations Fifty (42.2%) participants had a change in zibotentan trial medication and 22 (18.6%) participants permanently discontinued zibotentan treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in patients with type 2 diabetes, SGLT2 inhibition improves myocardial blood flow reserve measured using 13 N-ammonia PET/CT raising the possibility of a benefit from SGLT2 inhibition in the microvascular angina population. 29 This suggests a similar strategy to that used in the ZENITH-CKD trial combining low-dose zibotentan with an SGLT-2 inhibitor may be additive NMED-A129750A from the efficacy point of view and mitigate fluid retentive effects of the endothelin A antagonist. 18,30 Limitations Fifty (42.2%) participants had a change in zibotentan trial medication and 22 (18.6%) participants permanently discontinued zibotentan treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Dapagliflozin downregulated NADPH oxidase-dependent ROS production and malondialdehyde levels in mouse cardiac tissues [162], while canagliflozin reduces NADPH oxidase expression and lipid peroxides in the kidneys of diabetic rats [163]. But dapagliflozin treatment did not improve PON1 activity after 12 weeks in 15 patients with T2D [164], as well as HDL-mediated endothelial NO production after 4 weeks in eight patients with both T2D and CAD [165]. Further investigations with larger study populations are required to draw conclusive findings.…”
Section: Glucose Control Agentsmentioning
confidence: 93%
“…However, the mechanism by which they provide CV protection remains unclear. We recently demonstrated that treatment with the SGLT-2i dapagliflozin in T2D patients with stable coronary artery disease (CAD), can increase myocardial flow reserve (MFR), and we speculated that this increase could be caused by an improvement in coronary microvascular dysfunction [ 2 , 3 ]. Indeed, coronary microvascular dysfunction, in the absence of obstructive CAD and myocardial diseases, is considered a reversible condition, and MFR can be used to assess efficacy of treatment [ 4 ].…”
Section: Introductionmentioning
confidence: 99%